Errata: New measures of graph irregularity - Clive Elphick; Pawel Wocjan (Electronic Journal of Graph Theory and Applications (EJGTA), 2015)
This paper gives an errata to the paper "New measure of graph irregularity", Electronic Journal of Graph Theory and Applications {\bf 2}(1) (2014), 52-65.